Profile Of Tourette Syndrome In Children And Adolescents From A Tertiary Care Child Psychiatry Centre In India (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: Tourette Syndrome is a type of tic disorder that is not as rare as it was once thought to be. There is a paucity of literature on Tourette syndrome in children and adolescents in the Indian setting. The objectives of this study were to elucidate sociodemographic and clinical profile of children and adolescents with Tourette syndrome. Material and Method: The present study is a retrospective chart review of children and adolescents up to age 18 years diagnosed with Tourette Syndrome in a tertiary care centre, India. This sample is from a subset of a larger sample of case records of patients with a diagnosis of tic disorder, coded as F 95, according to ICD 10 from 1st January 2014 to 31st December 2017 (4 years duration). Results: The sample included 28 children. All of them were male, and the mean age of onset was 8.2 years. The period prevalence of Tourette syndrome was 0.22%. The entire sample received pharmacotherapy and the most common medication prescribed was Risperidone followed by Clonidine, Aripiprazole, Haloperidol, and Tetrabenazine. Majority (64.28%) of the sample had a comorbid condition. The most common comorbid conditions were Hyperkinetic Disorders followed by Obsessive Compulsive Disorder Specific and Specific Developmental Disorder of Scholastic skills Conclusion: Tourette syndrome can be a disabling condition in school-going children. There is a need for population-based studies for estimating its prevalence in Indian subcontinent., and there is also a great need to increase awareness and sensitize the public to seek help to improve the quality of life of children and adolescents with Tourette syndrome.